The investigation of cholinergic receptor muscarinic 1 activity in the rat ovary with induced ovarian hyperstimulation - Sanli, Cengiz; Atilgan, Remzi; Kuloglu, Tuncay; Pala, Sehmus; Ilhan, Nevin (Galenos Publ House, 2023)
Objective: We look at the immunoreactivity of cholinergic receptor muscarinic 1 (CHRM1) in the ovarian tissues of rats with ovarian hyperstimulation syndrome (OHSS) considering the possibility that the muscarinic activity may contribute to the pathophysiology of OHSS.Materials and Methods: In this study, 14 immature female Wistar Albino rats were divided into two groups at random. The rats were 22 days old. Rats in the control group (n=7) were 22 days old, while those in the OHSS group (n=7) received 10 IU follicle-stimulating hormone subcutaneously over the course of four days and 30 IU human chorionic gonadotropin (hCG) on the fifth day to induce ovarian hyperstimulation. All the rats were sacrificed after all the groups' ovaries and blood samples were collected at the conclusion of the experiment. The left ovarian tissues were kept in aluminum foil at-80 degrees C, while the right ovarian tissues were kept in 10% formalin. Tissue vascular endothelial growth factor (VEGF), interleukin (IL)-1j3 , IL-6, IL-10, tumor necrosis factor (TNF)-alpha and malondialdehyde (MDA) levels were measured by The Enzyme Linked Immunosorbent Assay technique in the ovarian tissues. CHRM1 immunoreactivity was scored immunohistochemically. Results: Ovarian weight, tissue IL-10, TNF-alpha , VEGF and MDA levels, and CHRM1 immunoreactivity were significantly increased in the OHSS group.Conclusion: Increased levels of CHRM1 activity may play a role in the pathophysiology of OHSS. With further studies, the effect of luteinizing hormone and hCG on the ovarian and hypothalamic cholinergic system can be further investigated, and useful information can be obtained in determining OHSS prevention strategies.
Ovaryan hiperstimülasyonu oluşturulan ratların overlerinde kolinerjik reseptör muskarinik 1 aktivitesinin araştırılması
Keywords: Rat; OHSS; cytokine; CHRM1